An in-vitro study on the anti-bacterial effect of honey on streptococcus sanguis from trauma-induced recurrent aphthous stomatitis, SY 2004-2005 - Gran, Paula Katrina T.
This research aimed to determine if commercial honey, which is easily accessible, inexpensive, naturally-produced, and pleasant to the taste, has an anti-bacterial effect on Streptococcus sanguis. An in-vitro experimental research design was utilized. Samples of the said bacteria were obtained from the RAS lesions of two orthodontic patients wearing braces. From these specimens, S. sanguis were isolated and identified. In the Disk Diffusion Method, honey was tested against the isolated bacteria under anaerobic conditions. Sterile disks dipped in different concentrations of honey were placed on plates lawned with the bacteria. After 24 hours, the plates were observed for zones of inhibition which would signify the anti-bacterial action of honey. The Kruskal-Wallis test was used to verify significance of results with a 10% level of confidence. Based on the zones of inhibition, 1%. 25%, 50%, 75%, and 100% concentrations of honey failed to inhibit the growth of S. sanguis.